Misconceptions Analysis of Students' Reflective-Impulsive Cognitive Style on Function Material - Aas Uswatun Hasanah; Arif Muchyidin; Budi Manfaat (MASI Mandiri Edukasi, 2023)
Students generally experience errors in two forms, namely conceptual and execution errors. Conceptual errors are related to students' lack of understanding, while execution errors occur when attempting to solve problems with incomplete procedures. This study aims to measure students' understanding of concepts after learning. The misconception analysis in this study used a four-tier diagnostic test. The results of this test provide five categories of student answers, namely understanding concept (understand), incomplete understanding (partial understanding), misconception, not understanding the concept (not understand), and cannot be coded (uncode). This research uses a mixed method. The data analysis phase is carried out by analyzing the data collected as Matching Familiar Figure Test (MFFT), four-tier diagnostic test data results, and in-depth interview data based on the results of the study concluded that in terms of students' reflective-impulsive cognitive style, impulsive students tend to experience higher misconceptions than reflective students.